The brain-derived neurotrophic factor (BDNF) val66met polymorphism differentially affects performance on subscales of the Wechsler Memory Scale – Third Edition (WMS-III) - Lamb, Yvette N.; Thompson, Christopher S.; McKay, Nicole S.; Waldie, Karen E.; Kirk, Ian J. (Frontiers in Psychology, 2015)
Single nucleotide polymorphisms in the brain-derived neurotrophic factor (BDNF) gene and the catechol-O-methyltransferase (COMT) gene influence brain structure and function, as well as cognitive abilities. They are most influential in the hippocampus and prefrontal cortex (PFC), respectively. Recall and recognition are forms of memory proposed to have different neural substrates, with recall having a greater dependence on the PFC and hippocampus. This study aimed to determine whether the BDNF val66met or COMT val158met polymorphisms differentially affect recall and recognition, and whether these polymorphisms interact. A sample of 100 healthy adults was assessed on recall and familiarity-based recognition using the Faces and Family Pictures subscales of the Wechsler Memory Scale – Third Edition (WMS-III). COMT genotype did not affect performance on either task. The BDNF polymorphism (i.e. met carriers relative to val homozygotes) was associated with poorer recall ability, while not influencing recognition. Combining subscale scores in memory tests such as the WMS might obscure gene effects. Our results demonstrate the importance of distinguishing between recall and familiarity-based recognition in neurogenetics research.